Kindle Fire HD for Dummies : pocket edition - Muir, Nancy, 1954- (--For dummies, 2013)
This book covers many of the feature in the original kindle fire, as well as the features that are new with the kindle fire HD. Though this book is forcused on kindle fire HD, wichever kindle fire model you own, you should find lost of advice and answers in this book.